PTSD Improvement Associated with Social Connectedness in Gerofit Veterans Exercise Program. Issue 4 (23rd December 2020) - Wilkins, Stacy Schantz; Melrose, Rebecca J.; Hall, Katherine S.; Blanchard, Erin; Castle, Steven C.; Kopp, Teresa; Katzel, Leslie I.; Holder, Alice; Alexander, Neil; McDonald, Michelle K.S.; Tayade, Arti; Forman, Daniel E.; et al.
Abstract : Objective: Post‐traumatic stress disorder (PTSD) is common in Veterans. Symptoms can perpetuate into late life, negatively impacting physical and mental health. Exercise and social support are beneficial in treating anxiety disorders such as PTSD in the general population, although less is known about the impact on Veterans who have lived with PTSD for decades. This study assessed associations between social connectedness, physical function and self‐reported change in PTSD symptoms among older Veterans specifically participating in Gerofit. Design: Prospective clinical intervention. Setting: Twelve sites of Veterans Affairs (VA) Gerofit exercise program across the United States. Participants: Three hundred and twenty one older Veteran Gerofit participants (mean age = 74) completed physical assessments and questionnaires regarding physical and emotional symptoms and their experience. Measurements: Measures of physical function, including 30‐second chair stands, 10‐m and 6‐min walk were assessed at baseline and 3 months; change in PTSD symptoms based on the Diagnostic Statistical Manual—5 (DSM‐5) assessed by a self‐report questionnaire; and social connection measured by the Relatedness Subscale of the Psychological Need Satisfaction in Exercise scale (PNSE) were evaluated after 3 months of participation in Gerofit. Results: Ninety five (29.6%) Veterans reported PTSD. Significant improvement was noted in self‐rated PTSD symptoms at 3 months ( P  < .05). Moderate correlation ( r = .44) was found between social connectedness with other participants in Gerofit and PTSD symptom improvement for those Veterans who endorsed improvement ( n = 59). All participants improved on measures of physical function. In Veterans who endorsed PTSD there were no significant associations between physical function improvement and PTSD symptoms. Conclusion: Veterans with PTSD that participated in Gerofit group exercise reported symptom improvement, and social connectedness was significantly associated with this improvement. In addition to physical health benefits, the social context of Gerofit may offer a potential resource for improving PTSD symptoms in older Veterans that warrants further study.